1997
DOI: 10.1007/s004390050349
|View full text |Cite
|
Sign up to set email alerts
|

Nance-Horan syndrome: linkage analysis in 4 families refines localization in Xp22.31-p22.13 region

Abstract: Nance-Horan syndrome (NHS) is an X-linked disease characterized by severe congenital cataract with microcornea, distinctive dental findings, evocative facial features and mental impairment in some cases. Previous linkage studies have placed the NHS gene in a large region from DXS143 (Xp22.31) to DXS451 (Xp22.13). To refine this localization further, we have performed linkage analysis in four families. As the maximum expected Lod score is reached in each family for several markers in the Xp22.31-p22.13 region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
(15 reference statements)
1
28
0
Order By: Relevance
“…Curiously, their unaffected brother had a profound mental impairment. A complete clinical and ophthalmological examination ruled out the possibility that MR in this subject may have been related to NHS, and the molecular analysis performed in this family [Toutain et al, 1997] clearly showed that he inherited a different haplotype from his affected brothers. Finally, the level of the single patient in family 4 showed that NHS may even be associated with high-normal intelligence.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Curiously, their unaffected brother had a profound mental impairment. A complete clinical and ophthalmological examination ruled out the possibility that MR in this subject may have been related to NHS, and the molecular analysis performed in this family [Toutain et al, 1997] clearly showed that he inherited a different haplotype from his affected brothers. Finally, the level of the single patient in family 4 showed that NHS may even be associated with high-normal intelligence.…”
Section: Discussionmentioning
confidence: 84%
“…No candidate gene has emerged either from the clinical pattern or from genetic data, although comparative mapping has allowed identification of a potential animal model in the mouse [Favor and Pretsch, 1990;Stambolian et al, 1994]. In a recent linkage study we refined the NHS gene localization in the Xp22.31-p22.13 region to a 15-18 cM interval between the loci DXS85 and DXS1226 [Toutain et al, 1997]. Genes for different specific and non-specific forms of XLMR have been mapped to the same region with overlapping localizations (Table IV).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has certain limitations: the efficiency of small family analyses is very low, if it is carried out based on the LOD value. The loci in the Xp22.31-p22.13 region associated with Nance-Horan syndrome was refined by linkage analysis (Toutain et al, 1997).…”
Section: Linkage Analysismentioning
confidence: 99%